Developing a new variety of kentia palms (Howea forsteriana): up-regulation of cytochrome b561 and chalcone synthase is associated with red colouration of the stems. Issue 2 (3rd April 2018) - Herraiz, Alba; Stokes, Laura; Turnbull, Colin; Hutton, Ian; Baker, William; Savolainen, Vincent
Abstract: The kentia palm ( Howea forsteriana ) is endemic to a 12 km 2 volcanic island in the Tasman Sea, Lord Howe Island. It is one of the most traded houseplants in the world. The typical kentia palm presents a dark green-coloured stem. Note that the stem is made of leaf rachis and petioles, which are intermingled towards the base. However, we discovered on Lord Howe Island a new biological variety that has a red stem. Red-stemmed palm species are known and highly demanded as decorative plants. However, these red palm horticultural varieties require tropical or subtropical conditions to grow, hence commercialization is limited. Thus, a red-stemmed variety of H. forsteriana may have tremendous market potential. Nonetheless, palm trees grow generally slowly and often reach maturity at 15–20 years old or later, which may make conventional strategies unsuitable for the propagation of a new variety. This difficulty needs to be addressed before commercialization can be achieved. Here, we found that anthocyanin is responsible for the red colouration of the stem in the new variety. Using RNA sequencing and quantitative PCR, we identified two gene isoforms displaying altered expression associated with this red colouration, encoding a cytochrome b561 and a chalcone synthase. The latter protein is known to be part of the anthocyanin biosynthesis pathway, which plays a central role in pigmentation in plants. The levels of cytochrome b561 transcripts accumulated were found to be well correlated with an increased anthocyanin concentration in the red stems.